A current perspective on apomixis in ferns. Issue 6 (29th November 2016) - Grusz, Amanda L.
Abstract: This review provides a synopsis of apogamous reproduction in ferns and highlights important progress made in recent studies of fern apomixis. First, a summary of the apomictic fern life cycle is provided, distinguishing between two pathways to diploid spore production that have been documented in apomictic ferns (premeiotic endomitosis and meiotic first division restitution) and briefly discussing the evolutionary implications of each. Next, recent trends in fern apomixis research are discussed, exposing a shift in focus from the observation and characterization of apomixis in ferns to more integrated studies of the evolutionary and ecological implications of this reproductive mode. Peer‐reviewed contributions from the past decade are then summarized, spanning the identification of new apomictic lineages through to the developmental, phylogenetic, and population genetic insights that have been made in studies of fern apomixis during that time. Gaps in our understanding are also discussed, including the extent and implications of recombinant apomixis in ferns, the possible reversibility of reproductive mode (from apomictic to sexual) in ferns, and the genomic causes and consequences of apomixis in seed free vascular plants. To conclude, future directions for fern apomixis research are proposed in the context of modern technological advances and recent insights from studies of apomixis in other groups.